Cross-sectional study on the prevalence of HPV antibodies in the general population of the Czech Republic - Hamsikova, Eva; Ludvikova, Viera; Stasikova, Jana; Tachezy, Ruth (Sexually transmitted infections, 2013)
OBJECTIVES: The assessment of the prevalence of antibodies to human papillomaviruses (HPV) in the healthy population is essential for effective planning of HPV vaccine implementation into the preventive programmes for HPV-associated diseases and for the prospective monitoring of the impact of HPV vaccines in the Czech population. METHODS: The seropositivity for HPV-6, 11, 16, 18, 31 and 33 virus-like particles was determined in sera from 3150 healthy individuals (age range 6-76 years) by means of enzyme-linked immunoassay. RESULTS: The seroprevalences for HPV-6, 11, 16, 18, 31 and 33 were 23.8%, 15.2%, 14.5%, 9.9%, 16.4% and 9.6% in women and 18.4%, 13.7%, 6.5%, 5.4%, 6.1% and 4.3% in men. For both genders, except for HPV11, these rates were age dependent. The prevalence of antibodies to HPV-16 and/or 18 reached the maximum of 27.0% in women 30-39 years of age and of 14.4% in men 50-59 years of age. The highest proportion of individuals' seropositive for any of the vaccine types HPV-6/11/16/18 was in 30- to 39-year-old women (50.0%) and in ≥ 60-year-old men (37.6%). Antibodies specific for vaccine HPV types were detected in 18.0% of children 6- to 14-year-old but in 26.4%, those older than 14 years. CONCLUSIONS: The data reveal age-specific differences in the HPV seropositivity rates between healthy women and men and support the implementation of HPV vaccination in the Czech Republic before the age of 13.
Keywords: Infant; Humans; kojenec; lidé středního věku; dítě; Child; Female; Aged; dospělí; ELISA; věkové faktory; séroepidemiologické studie; senioři; lidé; Enzyme-Linked Immunosorbent Assay; předškolní dítě; Papillomaviridae; Adult; Papillomavirus Infections; ženské pohlaví; Male; Middle Aged; Seroepidemiologic Studies; Adolescent; Czech Republic; infekce papilomavirem; Cross-Sectional Studies; protilátky virové; Antibodies, Viral; Age Factors; Česká republika; mužské pohlaví; Child, Preschool; průřezové studie; mladiství